Synergistic effect of powdered cashew sprout cum cotyledon and cereals on improving the biochemical and physical properties of extrudates. Issue 11 (9th August 2022) - Preethi, Palpandian; Mangalassery, Shamsudheen; Thanushree, Kodingar; Reddy, Sanikommu Vijay Rakesh; Pandiselvam, Ravi; Ramesh, Shunmugiah Veluchamy; Sachin, Agrahara Jannappa; Manikantan, Musuvadi Ramarathinam; Veena, Gonibeedu Lakshmana
Abstract: Sprouted cashew kernel and cotyledon are highly nutritious but remain underutilized or wasted in cashew plantations. Since, surface microbial contamination of sprouts is known, suitable processing methods are required to utilize it properly. In order to eliminate the microbial load of cashew sprout and cotyledon (CSC) and to modify it into most acceptable form, heat extrusion process was explored. Six feed flour composites were prepared comprising dried CSC powder, rice, and corn flour in the ratio of 0:75:25, 5:70:25, 10:65:25, 15:60:25, 20:55:25 and 25:50:25, with standard feed temperature (100°C), die diameter (4 mm), and screw speed (30 rpm). Among different feed flour combinations, 25:50:25 extrudate resulted in relatively high minerals content and suitable biochemical features while organoleptic qualities were best in the combinations viz., 5:25:70 and 10:25:65. The amalgamation of CSC powder in feed flour significantly influenced its physical properties viz ., color, functional, and textural properties. The hydrophobic nature of CSC powder aided in poor water absorption and solubility index of extrudates. The firmness, work on extension, cut force was high with incorporation of CSC powder. Presence of phenols and Maillard reaction due to heat processing has attributed for increased chroma ( c *) and hue angle ( h °) in the products. Novelty impact statement: The sprouted cashew nut and cotyledons of leftover raw cashew nuts at cashew plantation are a potential source of bio‐available minerals and healthy fats which could be used in the preparation of ready‐to‐eat extruded snacks. Incorporation of dried sprouted cashews and cotyledons at the rate of 5 to 15% was found to have better sensory characteristics with enhanced biochemical and physical properties.